Welfare Issues of Working Equines in India and Strategies for their Mitigation (Indian Journal of Animal Production and Management, 2024)
The working equines are important species in  India especially for the marginalised, socio economically weaker sections of society. Recent  years have witnessed a decline in their population  due to various reasons. Numerous work types of  working equids including mules, donkeys and  horses are found in different states as per work  requirement, climate and geography The animals of  these species face varied welfare problems. Non availability of adequate recourses, lack of  knowledge and skills of rearing communities,  metabolic and other diseases are the major welfare  problems encountered by these animals. This  paper discusses the welfare problems faced by the  working equines in India and suggests a  methodology for the assessment of welfare of these  animals. This paper also offers a detailed strategy  and actin plan for the improvement of welfare of these animals in India.
Keywords: equines welfare problems; assessment methodology; mitigation strategies